2020
DOI: 10.1136/gutjnl-2020-320786
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the gut-liver-immune axis to treat cirrhosis

Abstract: Cirrhotic portal hypertension is characterised by development of the decompensating events of ascites, encephalopathy, portal hypertensive bleeding and hepatorenal syndrome, which arise in a setting of cirrhosis-associated immune dysfunction (CAID) and define morbidity and prognosis. CAID describes the dichotomous observations that systemic immune cells are primed and display an inflammatory phenotype, while failing to mount robust responses to pathogen challenge. Bacterial infections including spontaneous bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 95 publications
0
95
0
Order By: Relevance
“…The gut microbiota harbours the largest pool of genetic material in the human body with more than 10 13 microbes with an extreme high metabolic activity (105,114). Nowadays, there is no doubt that changes in microbiota influence liver cirrhosis (summarized in several recent reviews) and that liver cirrhosis induces profound changes in the microbiota (107,115,116).…”
Section: Microbiota Effects On the Livermentioning
confidence: 99%
“…The gut microbiota harbours the largest pool of genetic material in the human body with more than 10 13 microbes with an extreme high metabolic activity (105,114). Nowadays, there is no doubt that changes in microbiota influence liver cirrhosis (summarized in several recent reviews) and that liver cirrhosis induces profound changes in the microbiota (107,115,116).…”
Section: Microbiota Effects On the Livermentioning
confidence: 99%
“…Although the gut barrier is inherently leaky, this leakiness increases after injury, such as alcohol-induced liver injury [1]. Then, a few gut-derived molecules or viruses are able to enter the portal vein and cause damage to the liver [2,3]. Once an infection or tissue damage occurs, homeostasis is broken, and the immune response of the liver is rapidly activated [4].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying immune deficits, exaggerated inflammatory response, liver dysfunction, and multiple hospitalizations make cirrhosis a prime candidate for suffering these negative consequences. 6,33 Therefore, the carriage rate and potential impact and determinants of ARGs needs to be defined in cirrhosis. Metagenomic and 16S rRNA gene analyses have consistently demonstrated a higher proportion of pathobionts in cirrhosis compared with controls, which worsen with progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…poor outcomes and higher mortality could be related to hepatic encephalopathy (HE) and infections, especially with drug-resistant organisms. 5,6 The summation of all antibiotic resistance genes (ARGs) and their precursors within a microbial community is termed a "resistome"; however, its clinical evaluation is currently limited to culture-based techniques. 7,8 Prior studies in cirrhosis have shown altered composition and function of intestinal microbiota, which can affect clinical outcomes.…”
mentioning
confidence: 99%